Perancangan Sistem Terintegrasi Multichannel Ecommerce Berbasis Website Pada PT XYZ - Yesa, Benedectus; Maharani, Herastia; Yonata, Yosi (Yayasan Petra Harapan Bangsa, 2022)
PT XYZ is a shoe distributor company in the city of Bandung that gets 700 shoe orders per day from 7 online stores that are active in several marketplaces. In the sales process, PT XYZ has problems when providing stock information to customers. Every time a sales transaction occurs, the stock information displayed in each marketplace channel must be updated one by one. This will take a lot of time and will pose a risk of inconsistency of stock information. To overcome this, a web-based multichannel e-commerce integrated system is designed that can process product data on each channel in the marketplace and integrate stock information. Based on the User Acceptance Test (UAT) with the UTAUT method, the proposed system gets an average score for the Performance Expectancy aspect of 94.3%, the Effort Expectancy aspect of 98.6%, and the Behavioral Intention aspect of 88.6%. The results of this test indicate that the integrated system can provide convenience for users in carrying out their duties, provide comfort in using the system, and make users want to use the system that has been designed.